2016
DOI: 10.1155/2016/1805414
|View full text |Cite
|
Sign up to set email alerts
|

Paliperidone Induced Hypoglycemia by Increasing Insulin Secretion

Abstract: We report the case of a 41-year-old woman with schizophrenia who developed persistent hypoglycemia following paliperidone administration. After discontinuing paliperidone, the hypoglycemia resolved, but symptoms of diabetes emerged. Therefore, it appears that the hypoglycemia induced by paliperidone may mask symptoms of diabetes. Paliperidone may induce hypoglycemia by increasing insulin secretion. This report could help elucidate the relationship between atypical antipsychotics and glucose metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The acute and chronic treatment with paliperidone did not alter serum insulin levels and β-cell function with the homeostatic model assessment (HOMA-B) (207,313,321). However, a case report showed increased insulin secretion, causing hypoglycemia in a schizophrenic female patient (322).…”
Section: Paliperidonementioning
confidence: 93%
“…The acute and chronic treatment with paliperidone did not alter serum insulin levels and β-cell function with the homeostatic model assessment (HOMA-B) (207,313,321). However, a case report showed increased insulin secretion, causing hypoglycemia in a schizophrenic female patient (322).…”
Section: Paliperidonementioning
confidence: 93%
“…A case report of hypoglycemia was excluded in one study because the patient had noninsulin-dependent diabetes mellitus and was taking risperidone concurrently with glyburide and sertraline [ 11 ]. Moreover, some studies have reported that risperidone induces hypoglycemia by increasing insulin secretion in nondiabetic patients with schizophrenia [ 12 , 13 ]. One of these reports indicated that a reduction in risperidone dose mitigated its effect of induced hypoglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study reported that switching from olanzapine to risperidone for the treatment of schizophrenia exacerbated a patient’s diabetes mellitus and hyperglycemia and resulted in decreased blood glucose levels and increased insulin levels [ 14 ]. Evidence suggests an association between risperidone use and a reduced risk of abnormalities during glucose–insulin homeostasis [ 13 , 14 ]. However, some reports have indicated that risperidone is associated with hyperglycemia and exacerbates preexisting diabetes and hypertriglyceridemia in patients on antipsychotic therapy [ 15 , 16 , 17 ] and that its long-term use induces nonalcoholic fatty liver disease-associated visceral adiposity [ 18 ] as well as liver damage [ 19 ] in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there are no reports on clozapine‐induced hypoglycemia, but there are case reports of the development of hypoglycemia with other antipsychotics 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 (Table 1 ). Most patients develop hypoglycemia induced by second‐generation antipsychotics, with olanzapine and quetiapine being the most frequent.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there are no reports on clozapine-induced hypoglycemia, but there are case reports of the development of hypoglycemia with other antipsychotics [4][5][6][7][8][9][10][11][12][13] (Table 1). Most patients develop hypoglycemia induced by The treatment of impaired glucose tolerance includes diet, exercise, and oral hypoglycemic medications.…”
Section: Melkersson Et Al Suggested That the Putative Mechanism Of Cl...mentioning
confidence: 99%